FAKTOR-FAKTOR DETERMINAN YANG MEMPENGARUHI PRESTASI BELAJAR SISWA - Simamora, Tohol; Harapan, Edi; Kesumawati, Nila (Graduate Program Magister Manajemen Pendidikan, 2020)
The purpose of this study was to determine the determinants that influence student learning achievement. The population in this study was class XII students, totaling 521 people. Sampling in this study was random sampling from 52 students. This research uses quantitative methods. Data collection is done by questionnaire, and documentation. Data were analyzed using inferential statistics, hypothesis testing with multiple linear regression, t test and f test. From the results of this study it can be concluded that 1) there is an influence of learning motivation on learning achievement, 2) there is an influence of learning interest on learning achievement, 3) there is no influence on the economic condition of the family on learning. achievement, 4) there is an influence on the level of parental education on learning achievement, 5) there is an influence on learning motivation, learning interest, family economic situation, parental education level on learning achievement.The implication for educators is to always motivate, and develop students' interest in learning and achievement.